Analysis of Interaction and Co‐editing Patterns amongst OpenStreetMap Contributors. Issue 5 (7th October 2013) - Mooney, Peter; Corcoran, Padraig
Abstract OpenStreetMap (OSM) is a very well known and popular Volunteered Geographic Information (VGI) project on the Internet. In January 2013 OSM gained its one millionth registered member. Several studies have shown that only a small percentage of these registered members carry out the large majority of the mapping and map editing work. In this article we discuss results from a social‐network based analysis of seven major cities in OSM in an effort to understand if there is quantitative evidence of interaction and collaboration between OSM members in these areas. Are OSM contributors working on their own to build OSM databases in these cities or is there evidence of collaboration between OSM contributors? We find that in many cases high frequent contributors ("senior mappers") perform very large amounts of mapping work on their own but do interact (edit/update) contributions from lower frequency contributors.